Performance Evaluation of Different Blood Levels of Crossbred Dorper Sheep and Farmers’ Perception Toward Crossbred Dorper Sheep in Central South Zone, Southern Ethiopia - Kebede Habtegiorgis; Deribe Gemiyo; Ayele Abebe; Addisu Jimma (Advances in Agriculture)
This study evaluates the growth performance of Dorper × indigenous crossbred sheep under semi-intensive management system and assesses farmers’ perceptions toward these crossbred lambs in southern Ethiopia. Performance data, namely, birth weight (BWT), weaning weight (WWT), and average daily weight gain from birth to weaning (ADG0-3), were collected from Mente Dubo breed evaluation and distribution (BED) site. To gather comprehensive information on sheep production systems and farmers’ perceptions, on-farm surveys were conducted in the Damot Pulasa, Damot Gae, and Damot Sore districts of Wolaita Zone using semistructured questionnaires. Data were analyzed using different procedures in Statistical Package for Social Sciences (SPSS) software. Analysis of growth performance revealed that, under the semi-intensive management system, the least squares means (LSM) for BWT, WWT, and ADG0-3 were 2.84 ± 0.06 kg, 15.40 ± 0.90 kg, and 137.78 ± 99 g/day, respectively, with a preweaning survivability rate of 77.7%. Farmers primarily raised sheep for income generation (index = 0.28) and as a form of savings (index = 0.25). Farmers expressed a preference for Dorper crossbred lambs due to their faster growth rates (odds ratio [OR] = 1.95, p <0.05) and docile behavior (OR = 2.12, p≤0.01). However, challenges such as increased susceptibility to disease and color-related drawbacks were also identified. In conclusion, there is a possibility of continuing cross-lamb production and disseminating it to selected pocket areas within the study areas. The breed could be promoted as an optional genetic material. To ensure better survival of crossbred lambs, it is important to integrate improved management systems, such as enhanced feed, housing, and healthcare.